Development and validation of the Crohn's disease patient-reported outcomes signs and symptoms (CD-PRO/SS) diary - Peter D. R. Higgins; Gale Harding; Nancy K. Leidy; Kendra DeBusk; Donald L. Patrick; Hema N. Viswanathan; Kristina Fitzgerald; Sarah M. Donelson; Marcoli Cyrille; Brian G. Ortmeier; Hilary Wilson; Dennis A. Revicki; et al. (SpringerOpen, 2018)
Abstract Background The clinical course of Crohn's disease (CD) and the effect of its treatment are monitored through patient-reported signs and symptoms (S&S), and endoscopic evidence of inflammation. The Crohn's Disease Patient-reported Outcomes Signs and Symptoms (CD-PRO/SS) measure was developed to standardize the quantification of gastrointestinal S&S of CD through direct report from patient ratings. Methods The CD-PRO/SS was developed based on data from concept elicitation (focus groups, interviews; n = 29), then refined through cognitive interviews of CD patients (n = 20). Measurement properties, including item-level statistics, scaling structure, reliability, and validity, were examined using secondary analyses of baseline and two-week clinical trial data of adults with moderate-to-severe CD (n = 238). Results Findings from qualitative interviews identified nine S&S items covering bowel and abdominal symptoms. The final CD-PRO/SS daily diary includes two scales: Bowel S&S (three items) and Abdominal Symptoms (three items), each scored separately. Each scale showed evidence of adequate reliability (α = 0.74 and 0.67, respectively); reproducibility (intraclass correlation coefficient > 0.80), and validity, with the last including moderate correlations with the Inflammatory Bowel Disease Questionnaire bowel symptom score and select items (ranging from r = 0.43-0.54). Scores distinguished patients categorized by patient global ratings of disease severity (p < 0.0001). Conclusions Results suggest the CD-PRO/SS is a reliable and valid measure of gastrointestinal symptom severity in CD patients. Additional longitudinal data are needed to evaluate the ability of the CD-PRO/SS scores to detect responsiveness and inform the selection of responder definitions.